Evolutionary origins of taste buds: phylogenetic analysis of purinergic neurotransmission in epithelial chemosensors. Issue 3 (March 2013) - Kirino, Masato; Parnes, Jason; Hansen, Anne; Kiyohara, Sadao; Finger, Thomas E.
Abstract : Taste buds are gustatory endorgans which use an uncommon purinergic signalling system to transmit information to afferent gustatory nerve fibres. In mammals, ATP is a crucial neurotransmitter released by the taste cells to activate the afferent nerve fibres. Taste buds in mammals display a characteristic, highly specific ecto-ATPase (NTPDase2) activity, suggesting a role in inactivation of the neurotransmitter. The purpose of this study was to test whether the presence of markers of purinergic signalling characterize taste buds in anamniote vertebrates and to test whether similar purinergic systems are employed by other exteroceptive chemosensory systems. The species examined include several teleosts, elasmobranchs, lampreys and hagfish, the last of which lacks vertebrate-type taste buds. For comparison, Schreiner organs of hagfish and solitary chemosensory cells (SCCs) of teleosts, both of which are epidermal chemosensory end organs, were also examined because they might be evolutionarily related to taste buds. Ecto-ATPase activity was evident in elongate cells in all fish taste buds, including teleosts, elasmobranchs and lampreys. Neither SCCs nor Schreiner organs show specific ecto-ATPase activity, suggesting that purinergic signalling is not crucial in those systems as it is for taste buds. These findings suggest that the taste system did not originate from SCCs but arose independently in early vertebrates.